Immunogenic evaluation of multi-epitope peptide-loaded PCPP microparticles as a vaccine candidate against Toxoplasma Gondii - Yilmaz-Ozturk, Rabia; Calik, Hilal; Yaman, Serkan; Ustun-Karatop, Eslin; Cakir-Koc, Rabia (ELSEVIER SCI LTD, 2023)
Toxoplasmosis is a major health problem and socioeconomic burden, affecting around 30-50% of the global population. Poly(dicarboxylatophenoxy)phosphazene (PCPP) polymer was chosen as adjuvant for the immunogenic peptide antigen. Peptide-loaded PCPP microparticles were synthesized via the coacervation method and the characterization studies of microparticles were conducted to determine their size, charge, morphology, encapsulation efficacy, and loading capacity. To evaluate in vivo efficacy of the vaccine candidate, Balb/c mice were immunized with the formulations. Brain and spleen tissues were isolated from animals to investigate cytokine levels, lymphocyte proliferation, and brain cyst formation. As a result, antibody and cytokine responses in groups immunized with peptide-loaded PCPP microparticles were found to be significantly higher when compared to the control group. In conclusion, our novel multi-epitope peptide-loaded PCPP microparticle-based vaccine formulation demonstrated considerable humoral and cellular immune responses against T. gondii and protected mice against T. gondii infection during Toxoplasmosis.
Keywords: Immunity; Microparticle; PCPP; Peptide-based vaccine; Toxoplasma gondii; PROTECTIVE IMMUNITY; EFFICACY; Immunology; Microbiology; Veterinary Sciences